Mechanical Vibration of Visco-Elastic Plate With Thickness Varation - Khanna, Anupam; Sharma, Ashish Kumar (International Journal of Applied Mathematical Research, 2012)
A mathematical study or model is constructed with an aim to assist the design engineers for the making of various structures used in the satellite and aeronautical engineering. Visco- elastic plates are being increasingly used in the aeronautical and aerospace industry as well as in other fields of modern technology. To use them a good understanding of their structural and dynamical behavior is needed. In the modern technology, the plates of variable thickness are widely used in engineering applications. A mathematical model is presented for the use of engineers and research workers in space technology; have to operate under elevated temperatures. Rayleigh Ritz approach is applied for the solution of the problem. Fundamental frequencies and deflection functions are calculated for first mode of vibration of a clamped plate with diverse values of thermal gradient and taper constants.